Elimination and replacement of canine reservoir in an area endemic for visceral leishmaniasis - Nunes, Caris Maroni [UNESP]; Burattini, Marcelo Nascimento (Soc Brasileira Medicina Tropical, 2008)
This work reviews studies about dog culling in Brazilian endemic areas for visceral leishmaniasis, as well as studies on dog replacement after euthanasia in areas where it is indicated as a control measure for this zoonosis.
Keywords: Visceral leishmaniasis; Culling; Canine replacement